Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Behavioral weight loss interventions (BWL) consisting of remote coaching and self-monitoring have limited effectiveness in breast cancer (BC) survivors. We conducted a single-arm phase II study evaluating addition of Contrave® for <5% weight loss (%WL) after 2-months of BWL. Women with prior stage 0-III BC and BMI ≥27 kg/m2 were eligible and initiated BWL. We collected weight, patient-reported outcomes, and labs at baseline, 2- and 6-months. At 2-months, participants with ≥5%WL (FAST-BWL) continued BWL; those with <5%WL (SLOW-BWL) received BWL+Contrave®. The primary endpoint was proportion of SLOW-BWL with ≥5%WL at 6-months, with 30 participants providing 80% power with 5% type I error. Paired t-tests, Kruskal-Wallis tests and mixed-effects models were utilized. Of 55 participants, 2 withdrew prior to 2-months. At 2-months, 15 (28.3%) were FAST-BWL with mean%WL (SD) of 7.2% (1.5); and 38 (71.7%) were SLOW-BWL with mean%WL of 1.2% (2.2). Mean%WL between 2-6 months was similar in SLOW-BWL (3.8%±3.6) and FAST-BWL (3.6%±2.6). At 6-months, mean%WL was 5.1% (2.9) for SLOW-BWL and 10.8% (3.5) for FAST-BWL; 13/15 (86.7%) FAST-BWL and 16/38 (42%) SLOW-BWL had ≥5%WL. Physical function and pain improved with ≥5%WL (p=0.03 and p=0.02, respectively). SLOW-BWL had improved HbA1c (p=0.003) and triglycerides (p=0.04). Gastrointestinal symptoms were reported in 74% of SLOW-BWL. Of six withdrawals on Contrave®, one was due to adverse events. Adding Contrave® for BC survivors with minimal initial benefit from BWL results in clinically meaningful weight loss (≥5%) in 42% following 6 months of treatment, which also improves selective cardiometabolic risk factors.